Diálogo sobre o cinema na educação do campo: uma proposta inclusiva - MONTEIRO, Paulo Gabriel Nascimento (2022)
The cinema appreciated in different ways and has very specific goals, be it an artistic and/or aesthetic manifestation or even a projection of a possible fantasy, a hobby that escapes reality. Opposing all the views cited, it's possible to relate cinema to education, both in the possibility of dialoguing with experiences and views of the world in a more simplified way, as well as with more complex social problems or susceptible to a slightly more critical debate, making subjects difficult to understand accessible. The Cinema is able to deliver a certain efficiency in this proposal, in addition to promoting interdisciplinarity in a space that is increasingly common to “separate” certain subjects. For farmers, peasants and others who live in rural spaces, cinema can be a good alternative for inserting these subjects in the dialogue, since through it (cinema) it's possible to direct a lot of information that is easy to understand. Therefore, it's important to understand these subjects, the politics of the modality in which they are inserted, their processes of struggle to guarantee rights, their specificities and promote discussions about cinema as an educational proposal, a facilitating tool in this teaching-learning process, in addition to to enable the formation of critical positions and possible social transformations, from the awareness of groups that were once denied due informations and how they contribute to the environment around them or to the society that they are part.